Clinical and Laboratory Features of Patients with Acquired Thrombotic Thrombocytopenic Purpura: Fourteen Years of the Milan TTP Registry - Mancini, Ilaria; Pontiggia, Silvia; Palla, Roberta; Artoni, Andrea; Valsecchi, Carla; Ferrari, Barbara; Mikovic, Danijela; Peyvandi, Flora; for the Italian Group of TTP Investigators (Thrombosis and Haemostasis, 2019)
Acquired thrombotic thrombocytopenic purpura (TTP) is a rare thrombotic microangiopathy caused by the immune-mediated severe deficiency of ADAMTS13. We hereby report the demographic and disease-related data of acquired TTP patients recorded in the Milan TTP Registry (www.ttpdatabase.org). We performed a cross-sectional study of 302 individuals enrolled in our registry for an acute episode of acquired TTP occurred between 2002 and 2015 (female 77%; median age at onset 40 years, interquartile range: 30–50). Twenty per cent of patients had concomitant autoimmune disorders. Among potential triggers of acute episodes, infections were the most prevalent (27%), followed by estroprogestinics use and pregnancy (5 and 4% of women, respectively). At presentation, systemic (72%), bleeding (68%) and neurological (43%) symptoms were the most frequent, whereas a lower prevalence of renal (18%) and cardiovascular (10%) signs and symptoms was observed. Almost all acute events were treated by plasma exchange and steroids, and 15% by rituximab. Exacerbation of acute TTP occurred in 15% of events. The TTP-related mortality was 5%. In survivors, the median number of plasma exchange procedures to remission was 9 (interquartile range: 6–14), longer for first events than relapses (median difference 3, 95% confidence interval: 2–4). Of 251 survivors of the first TTP episode with at least a 6-month follow-up, 55% had a relapse. In conclusion, acquired TTP is a severe disease with highly variable clinical presentation, usually requiring a long hospitalization. The Milan TTP Registry represents a powerful tool to improve our knowledge and management of acquired TTP.
Keywords: ADAMTS13; diagnosis management; register; thrombotic microangiopathy; thrombotic thrombocytopenic purpura